A simple technique for the preparation of thin foils in aluminium and its alloys - Hacking, R. G. (College of Aeronautics, 1967)
Transmission electronmicroscopy using thin metal foils depends largely upon the success of the techniques used for the preparation of the thin foil. Many methods have been developed successfully for a wide range of materials and these have been discussed in detail elsewhere. These methods are as diverse as mechanical polishing, ionic bombardment and electrochemical thinning. The basis of one of the simplest of these methods is to produce a small sample of the metal and to thin this by a combination of mechanical polishing and electrolytic dissolution … [cont.].